Study of the red cell indices, hemogram and platelet variations in anaemic (<10gm%) patients by automatic cell counter in a tertiary care centre, Ahmednagar, Maharashtra, India - Jadhav, Saili U.; Khaparde, Sadhana (International Journal of Research in Medical Sciences, 2017)
Background: Anemia is not a disease but it is the expression of underlying diseases and from the treatment point of view, it is necessary to identify the cause of anemia. The definition of anemia is as decrease in the number of red blood cells or the decreased percentage of hemoglobin in the blood. Anemia is such an important issue affecting a large population in India as well as worldwide, Hence, the present study was conducted to evaluate the red cell indices, haemogram and study the relation of platelet count with anaemia in anaemic (<10gm%) patients by automatic cell counter in Vikhe Patil Medical hospital. Methods: It was a prospective cross-sectional study. The sample size of research project was 100 patients, included according to the inclusion and exclusion criteria. Results: In present study, equal numbers of patients suffer from macrocytic normochromic anemia and hyperchromic anemia, that is, 8 patients of each. Out of 100 patients, 61% patients showed decreased platelet count. Maximum percentage of anaemic patients showed decreased platelet count in the range of 2.5-1.5 lakhs. Least percentage of patients (16%) showed platelet count less than 0.5 lakhs/cmm3. Conclusions: Screening for anaemia, treatment of anaemic women, and availability and use of food fortification (wheat flour with iron and folic acid), milk, sugar and salt with iron to build long term iron stores remains the key to reduce anemia in adolescent and pregnant women. Consumption of cheap iron-rich foodstuffs should be promoted. Effective poverty alleviation and hookworm prevention programs are also important.